A Microribbon Hybrid Structure of CoOx‐MoC Encapsulated in N‐Doped Carbon Nanowire Derived from MOF as Efficient Oxygen Evolution Electrocatalysts. Issue 48 (9th November 2017) - Huang, Tan; Chen, Yu; Lee, Jong‐Min
Abstract: Developing highly efficient electrocatalysts for oxygen evolution is vital for renewable and sustainable energy production and storage. Herein, nitrogen‐doped carbon encapsulated CoOx‐MoC heterostructures are reported for the first time as high performance oxygen evolution electrocatalysts. The composition can be tuned by the addition of a Mo source to form a nanowire‐assembled hierarchically porous microstructure, which can enlarge the specific surface area, thus exposing more active sites, facilitating mass transport and charge transfer. Moreover, it is demonstrated that the formation of CoOx‐MoC heterostructures and the resulting synergistic effect between MoC and Co facilitate the reaction kinetics, leading to significantly improved oxygen evolution reaction (OER) activity with an onset overpotential of merely 290 mV, and a low overpotential of 330 mV to afford a current density of 10 mA cm −2 . The well‐constructed microarchitecture contributes to superior long term stability electrochemical behaviors. This work provides a facile strategy via composition tuning and structure optimization for the development of next‐generation nonprecious metal‐based OER electrocatalysts. Abstract : The microribbon hybrid structure of CoOx‐MoC encapsulated in N‐doped carbon nanowires exhibits a plethora of interconnected channels and well‐arrayed catalytic sites, which show structural advantages. Moreover, the synergistic effect between CoOx and MoC is found to improve electrochemical performance. Therefore, these structural and compositional superiorities contribute to their highly outstanding oxygen evolution catalytic behavior.